Synthesis of Pectiniform Polyurethane-Modified Polycarboxylate and Its Preliminary Application in Ultrahigh-Performance Concrete - Shuncheng Xiang; Yingli Gao (Advances in Civil Engineering)
In this paper, modified polyurethane prepolymer was synthesized by the segmental synthesis method using isophorone diisocyanate (IPDI), hydroxyl-terminated silicone, and polyether glycol dimethylolpropionic acid as raw materials. After that, pectiniform polycarboxylate, of which side chains were in roughly the same polymerization degree and main chains were in different lengths, was synthesized at normal temperature in the complex initiation system of H2O2, APS, sodium bisulfite, and Vc. Then, compared with commercial Sika polycarboxylate, their applications in ultrahigh-performance concrete (HUPC), including flowability, strength, drying shrinkage, and autogenous shrinkage, were investigated. The results showed that, due to the molecular structure of polyorganosiloxane, the synthesized polycarboxylate could be better dispersed. Dosage of silica fume could effectively improve the compressive strength of UHPC, while slag had a certain negative impact on its strength. Incorporation of slag and silica fume could effectively reduce the dry shrinkage of UHPC.